Strategi Marketing Mix Baitul Mal wa Tamwil (BMT) Unit Gabungan Terpadu (UGT) Sidogiri Pasuruan - Kirom, Cihwanul (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2016)
Within the business realm, marketing is a key factor which determines the success of distribution. Therefore, strategy and innovation are a necessity. Marketing activity would ensure whether a certain product is delivered to the costumers. In order to achieve the desired goals of marketing, it is important to manufacturers to follow a set of marketing processes, which comprise market overview, marketing strategy, marketing mix, and evaluation. Marketing mix is a set of strategies consist of product, price, promotion, and distribution, which guarantee the success of marketing activities. All of these aspects are intended to attain responses from the targeted market. The article seeks to discuss the marketing mix strategy implemented by BMT UGT Sidogiri Pasuruan based on four âPsâ, namely product, price, place, and promotion. The study finds that the marketing mix strategy employed by BMT UGT has met the costumersâ needs in terms of product strategy, pricing strategy, distribution strategy, and promotion strategy. The study also concludes that the proper implementation of marketing mix strategy and its compatibility with Islamic sharÃ®Ê»ah as well as the organizationâs obedience towards Islamic business ethics are among pivotal factors that have significantly influenced the development of BMT UGT Sidogiri